A High efficacy of Artemether–Lumefantrine and Artesunate-Amodiaquine for the treatment of uncomplicated falciparum malaria in Massokory, Mondo and Dourbali provinces (Chad). - Hamit, Mahamat Alio (British Journal of Healthcare and Medical Research, 2022)
Artemether-Lumefantrine (AL) and Artesunate-Amodiaquine (ASAQ) are recommended for the treatment of uncomplicated malaria in Chad. The objective of this study was to evaluate the High efficacy of Artemether–Lumefantrine and Artesunate-Amodiaquine for the treatment of uncomplicated falciparum malaria in Massokory, Mondo and Dourbali provinces (Chad).The study was carried out in 2019, 1113 patients children aged from 6 to 60 months were randomly assigned treatment with Artemether-Lumefantrine and Artesunate-Amodiaquine and followed up for 28 days. Primary endpoint was the treatment efficacy over 28 days. The early treatment failure was (0.13%) in AL group and (0.17%) in ASAQ group. No early clinical failure was found. Adequate clinical and parasitological responses were significantly higher in Artesunate-Amodiaquine group (ASAQ) (99.82% versus (99.10%) in Artemether-Lumefantrine (AL) group, p = 0.0009). All treatments had a similar and good tolerability profile that confirm the high efficacy of the first- and the newly recommended alternative ACT for treatments for uncomplicated falciparum malaria in Chad. The high parasite density clearance suggests absence of suspected artemisinin resistance, defined as delayed parasite clearance